2008
DOI: 10.1074/jbc.m700766200
|View full text |Cite
|
Sign up to set email alerts
|

A Plant Ca2+ Pump, ACA2, Relieves Salt Hypersensitivity in Yeast

Abstract: Stress responses in both plants2؉ transient and survival of cultures subjected to NaCl stress was similar for the ACA2 transformant and K601. However, whereas K601 maintained low cytosolic Na ؉ predominantly by pumping it out across the plasma membrane, the transformant sequestered Na ؉ in internal organelles. This sequestration requires the presence of an endomembrane Na ؉ /H ؉ -antiporter, NHX1, which does not play a significant role in salt tolerance of wild type yeast except at acidic pH. Transcript levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 57 publications
2
26
0
1
Order By: Relevance
“…Interestingly, in the present study, susceptible plants showed an average low expression of TIP throughout pathogen progression, further validating oxidative injury that resulted in xylem clogging and water stress. ACAs are also thought to regulate salt stress along with calcium dependent protein kinases (CDPKs) and calmodulin, which act as negative regulators [81][82]. Present study showed enhanced expression of ACA in resistant plants, suggesting a role for CDPKs and calmodulin in host defense.…”
Section: Discussionmentioning
confidence: 56%
“…Interestingly, in the present study, susceptible plants showed an average low expression of TIP throughout pathogen progression, further validating oxidative injury that resulted in xylem clogging and water stress. ACAs are also thought to regulate salt stress along with calcium dependent protein kinases (CDPKs) and calmodulin, which act as negative regulators [81][82]. Present study showed enhanced expression of ACA in resistant plants, suggesting a role for CDPKs and calmodulin in host defense.…”
Section: Discussionmentioning
confidence: 56%
“…PMC1 overexpression enhanced Al and Ca tolerance in wild-type yeast and the pmc1 mutant (Figure 3). Endomembrane Ca 2+ -ATPases appear to be important for intracellular Ca 2+ distribution [28], [40], [56]. Recent studies have shown that PMCA overexpression depletes intracellular Ca 2+ stores and induces apoptosis through the mitochondrial pathway in clonal β-cells [57].…”
Section: Discussionmentioning
confidence: 99%
“…Al toxicity strongly affects intracellular Ca homeostasis, which is another mechanism that is hypothesized to cause Al injury [1], [13]. The sensitivity and response of cells to various stresses, including Al, is dependent on the ability of cells to adequately sequester Ca 2+ into their internal stores [28], [29], [30]. Ca 2+ is stored in the cell wall and in intracellular organelles, including the endoplasmic reticulum (ER), mitochondria, and vacuoles.…”
Section: Introductionmentioning
confidence: 99%
“…Although double mutants lacking both Pmr1p and the vacuolar membrane Ca 2+ -ATPase Pmc1p are inviable irrespective of Ca 2+ concentration, triple mutants also defective in the Ca 2+ -binding subunit of calcineurin Cnb1p are viable but require exogenous Ca 2+ for growth (Cunningham and Fink, 1994; Sze et al, 2000). These pmr1 pmc1 cnb1 triple mutants are hypersensitive to high Na + levels but this salt hypersensitivity can be overcome by heterologous expression of an endoplasmic reticulum-located Ca 2+ -ATPase (Anil et al, 2008). In any consideration of calcium homeostasis, it is also important to remember that fungal vacuoles are a major site of Ca 2+ storage (Dunn et al, 1994; Klionsky et al, 1990).…”
Section: Introductionmentioning
confidence: 99%